Characterization of wheat oligo‐tiller mutant ot2 and fine mapping of the mutant gene Taot2 - Chenxi Wang; Jiaxing Bai; Hongchun Xiong; Yongdun Xie; Jiayu Gu; Linshu Zhao; Huiyuan Li; Yuping Ding; Xinmei Guo; Huijun Guo; Luxiang Liu (The Plant Genome, 2025)
Abstract Tiller number is a crucial determinant of grain yield in wheat (Triticum aestivum L.), and identifying functional alleles can enhance our understanding of wheat tiller development. Here, we describe the ot2 wheat mutant, which exhibits a 91% reduction in tiller number compared to the wild type and displays inhibited tiller bud differentiation from the 2–3 leaf stage. Bulked segregant analysis combined with exon sequencing mapped the Taot2 gene to chromosome 1BL. Fourteen kompetitive allele‐specific PCR markers were developed and utilized to narrow down the region containing Taot2 to a 2.22 Mb interval. This region encompasses 39 high‐confidence genes. Through transcriptomic analysis and functional gene investigation, TraesCS1B03G1126300 was identified as the candidate gene, encoding an auxin‐responsive protein of the auxin/indole‐3‐acetic acid family. Our findings provide the foundation for map‐based cloning of Taot2, a novel wheat tiller gene, and offer valuable insights into wheat tiller bud initiation.